2002
DOI: 10.1046/j.1365-2249.2002.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

CD14-dependent and -independent cytokine and chemokine production by human THP-1 monocytes stimulated byStreptococcus suiscapsular type 2

Abstract: SUMMARYStreptococcus suis capsular type 2 is an important aetiologic agent of swine meningitis, and it has been highlighted as a cause of occupational disease leading to meningitis and fulminant sepsis in humans. The objective of the present work was to study the ability of S. suis type 2 to induce the release of tumour necrosis factor alpha (TNF-a), interleukin-1 (IL-1), IL-6, IL-8 and monocyte chemotactic protein one (MCP-1) by human monocytic THP-1 cells. The induction of these five cytokines was doseand in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
91
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 47 publications
15
91
0
1
Order By: Relevance
“…Segura et al showed that the release of TNFα, IL1, IL6, and MCP1 was increased after 48 hours' stimulation with 1 μg/mL LPS, the concentration for each mediator being higher than the level shown in the present study, but this difference could be explained by the difference in the concentration of LPS used for cell activation (1 μg/mL compared with 100 ng/mL in our experiments). 33 Our study demonstrates that Lipo/GOT completely blocked the secretion of IL1β, IL6, TNFα, and MCP1 compared with free GOT, which did not decrease the secretion of these cytokines/chemokines induced by LPS. This effect of Lipo/GOT vs free GOT may be explained by increased cellular internalization of the compound when it is formulated into Lipo and gradual intracellular release, whereas the free compound acts very rapidly or is committed to intracellular degradation.…”
Section: Discussionmentioning
confidence: 51%
“…Segura et al showed that the release of TNFα, IL1, IL6, and MCP1 was increased after 48 hours' stimulation with 1 μg/mL LPS, the concentration for each mediator being higher than the level shown in the present study, but this difference could be explained by the difference in the concentration of LPS used for cell activation (1 μg/mL compared with 100 ng/mL in our experiments). 33 Our study demonstrates that Lipo/GOT completely blocked the secretion of IL1β, IL6, TNFα, and MCP1 compared with free GOT, which did not decrease the secretion of these cytokines/chemokines induced by LPS. This effect of Lipo/GOT vs free GOT may be explained by increased cellular internalization of the compound when it is formulated into Lipo and gradual intracellular release, whereas the free compound acts very rapidly or is committed to intracellular degradation.…”
Section: Discussionmentioning
confidence: 51%
“…It is reasonable to explain this phenomenon by the thicker capsule of the ⌬covR strain, since it has been reported that the capsular polysaccharide (CPS) of S. suis protects against phagocytosis and against the bactericidal activity of leukocytes (6,9,48,59,62,63,79). The work of Segura et al demonstrated that S. suis serotype 2 is able to interact with MONOs of human origin, inducing the release of large amounts of the proinflammatory cytokines (61).…”
Section: Discussionmentioning
confidence: 99%
“…First, encapsulated S. suis is able to adhere to the surface of phagocytes, and the CPS itself is involved in such adhesion (41). Second, encapsulated S. suis is able to induce the release of proinflammatory cytokines by phagocytes by an adhesion-dependent process (42,43). However, the levels of induced cytokines are lower than those induced by the nonencapsulated mutant (42,48).…”
Section: Discussionmentioning
confidence: 99%